Relationship between environmental management systems implementation and environmental performance: Findings from Turkish EMS certificated businesses - Halis, Muhsi̇n; Halis, Mine (Canadian Institute for Knowledge Development, 2016)
Gradually, increasing environmental awareness has increased the demand for goods and services. These manufactured goods and services are made in compliance with environmental standards to protect and enhance environmental assets and natural resources as important competitive factors. Numerous standards and legal legislations have been developed to guide businesses on environmental issues. Therefore, various businesses sectors are more inclined to develop and implement environmental policies these days. Many of these policies are developed with the guidance of ISO 4001 — Environmental Management Systems (EMSs). The businesses which have adopted the standards of the EMSs have to protect the environment and ensure its continuity. Thus, businesses require the reflection of environmental management activities on businesses performance evaluation in terms of price competitiveness and cost effectiveness. To this end, this research aims to study Turkish businesses which have adopted and got EMS certification and accordingly analyze the development and implementation of EMS and how its implementation in turn affects environmental performance. Descriptive Statistics, Correlation, and Linear Regression Analyses were used to assess the association between EMS implementation and environmental performance. The results revealed that EMS implementation has a significant positive impact on environmental performance.
Keywords: 9. Industry and infrastructure; 13. Climate action; 4. Education; 8. Economic growth; 11. Sustainability; 7. Clean energy; 12. Responsible consumption